Cranial hypertension syndrome in children (report of a case of hydrocephalus) - Krumdieck, Carlos F. (1929)
Among the diseases of infants, there is a special clinic which by their appearance, for the truly monstrous deformities that may present difficult and its treatment, provides a strong interest both from the point of view neurological and pediatric; I mean ventricular hydrocephalus.